Peran Guru sebagai Agen Perubahan dalam Pencegahan Bullying di Sekolah - Nantana, M. Gebryna Rizki; Suciptaningsih, Oktaviani Adhi; Bari, Miftahul (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: Bullying is an action or behavior that is unacceptable and dangerous. We often encounter a culture of bullying in educational environments, such as schools, with perpetrators who are felt to be more senior or have a big influence, who are irresponsible. When bullying cases occur at school, the role of teachers in preventing and handling bullying cases is really needed. Thus, we all need to know that acts of bullying must be anticipated as optimally as possible in order to minimize the negative influence that will occur on student development. The aim of this research is to explore and review the role of teachers in preventing and handling bullying behavior at Bahrul Magfiroh Middle School. In this research, researchers used a qualitative research approach, with a case study method. The results of research show the importance of the role of teachers in preventing and handling bullying cases in schools which include: 1). Teachers as mediators in preventing and handling bullying, 2). application of a positive disciplinary attitude, 3). as well as providing advice and guiding students who have a tendency towards bullying behavior. In this way, when the teacher's role is known and understood by teachers as a preventative and handling measure, bullying in schools can be minimized and even prevented so that negative impacts do not have more serious effects.